2018
DOI: 10.1108/ijbm-04-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Personnel capability and customer satisfaction as predictors of customer retention in the banking sector

Abstract: Purpose The purpose of this paper is to report the findings of a study undertaken to understand customer satisfaction and customer retention in business-to-consumer markets. The study investigates the effect of personnel capability and customer satisfaction on customer retention in the banking sector. The influence of the control variable (gender) on customer retention and mediating role of customer satisfaction has also been examined. Design/methodology/approach The study has used structural equation modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
34
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 61 publications
10
34
0
4
Order By: Relevance
“…Satisfied customers are believed to make more repeat purchases and to share their positive experiences with others [37], which in the end is turning become as customer retention. The more satisfied the customers are, the higher their retention is [8]. This statement in-line with previous research that showed that customer satisfaction has a positive effect on customer retention [8], [38].…”
Section: Retentionsupporting
confidence: 91%
See 4 more Smart Citations
“…Satisfied customers are believed to make more repeat purchases and to share their positive experiences with others [37], which in the end is turning become as customer retention. The more satisfied the customers are, the higher their retention is [8]. This statement in-line with previous research that showed that customer satisfaction has a positive effect on customer retention [8], [38].…”
Section: Retentionsupporting
confidence: 91%
“…The more satisfied the customers are, the higher their retention is [8]. This statement in-line with previous research that showed that customer satisfaction has a positive effect on customer retention [8], [38]. Thus, the hypothesis developed as follows: H6: Satisfaction has a positive effect on customer retention.…”
Section: Retentionsupporting
confidence: 80%
See 3 more Smart Citations